Analisis Faktor-Faktor Yang Mempengaruhi Auditor Dalam Memberikan Opini Audit Going ConcernStudi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Periode 2012-2014 - Permana, Sera Yuli; , Drs. Wahyono, MA, Ak (2016)
This research was aimed to identify the influence of debt default, prior audit opinion, liquidity ratio, leverage ratio to going concern audit opinion at manufacture company was enlisted in Effect Exchange Indonesia (BEI) start 2012 until 2014. This research population was entire manufacture Company what was enlisted in Effect Exchange Indonesia (BEI) start 2012 until 2014. Sampling method was using purposive sampling method. The data technique analyse was using the logistic regression analyze. Research result shows that determination coefficient value get obtained 0,683 this means that 68,3% going concern audit opinioncan be influencedebt default, prior audit opinion, liquidity ratio, and leverage ratio, the rest equal to 31,7% can be explained the other variable outside in this research. Hyphothesis result shows that debt default and prior audit opinion has significant influence on going concern audit opinion, while liquidity ratio, and leverage ratio hasn't significant influence on going concern audit opinion.